Komposisi Fitoplankton Pada Tambak Kerang - Ken Suwartimah; Ika Desie Wulandari; Retno Hartati; Sri Redjeki (Universitas Diponegoro, 2017)
This study aims to determine to determine the species composition, abundance and community structure of phytoplankton in shellfish aquaculture ponds blood (Anadara granosa) in Menco, District Wedung, District Demak.Metode used in this study is Diskriptif method, determination of the location of the study is purposive sampling Methods, namely the determination of the sampling locations should be based on consideration, the station I to III of the sampling stations representing keseluruan research area. Marine research station is Blood Shellfish Farming in Hamlet Menco. Station is divided into three stations, with making four periods. Environmental parameters taken include: salinity, temperature, pH, DO, nitrate, phosphate, dissolved oxygen, organic materials. The results of the study, found 19 genera of phytoplankton. Phytoplankton abundance 2596-18844 cells / L. Diversity index (H ') based on the total period ranged from 1.098 to 1.837. On January 18-March 3, 2014, categorized into the diversity index medium. Uniformity index (e) the entire period ranged from 0.616 to 0.999. Fitoplankton atau mikroalga merupakan makanan utama kerang di tambak. Penelitian ini bertujuan untuk mengetahui komposisi jenis, kelimpahan, dan struktur komunitas fitoplankton pada tambak budidaya kerang darah (Anadara granosa) di Menco, Kecamatan Wedung, Kabupaten Demak. M etode yang digunakan dalam penelitian ini adalah metode Deskriptif. Sampel fitoplankton diambil dari Tambak Kerang Darah selama empat periode. Parameter lingkungan sebagai data penunjang adalah salinitas, suhu, pH, DO, nitrat, fosfat, oksigen terlarut, bahan organik. Hasil penelitian menjunjukkan terdapat 19 genus fitoplankton, dengan kelimpahan 2.5-18.8x103sel.L-1. Indeks keanekaragaman (H’) berdasarkan total keseluruhan periode berkisar antara 1,098-1,837. Pada tanggal 18 Januari-3 Maret 2014, dikategorikan masuk dalam indeks keanekaragaman sedang. Indeks keseragaman (e) keseluruhan periode berkisar antara 0,616–0,999.